KREATIVITAS GURU PAI DALAM MENGGUNAKAN MEDIA PEMBELAJARAN DI SMKN 4 PAYAKUMBUH - Raisa Juliandari; Muhiddinur Kamal; Junaidi Junaidi; Salmiwati Salmiwati (Universitas Pahlawan Tuanku Tambusai, 2022)
This study discusses the creativity of PAI teachers in using learning media at SMKN 4 Payakumbuh. This study aims to determine the creativity of PAI teachers in using learning media at SMKN 4 Payakumbuh, the supporting and inhibiting factors of PAI teachers in using learning media at SMKN 4 Payakumbuh. This study uses a type of field research (field research) with a qualitative descriptive type, namely research aimed at describing and analyzing the phenomenon of events, social activities, attitudes, beliefs, thoughts of people individually and in groups. Data collection techniques in this study were observation, interviews and documentation. Furthermore, the data analysis technique here is where the author takes steps such as data reduction, display (data presentation), drawing conclusions and verification. The results of the study prove that: First, the creativity of PAI teachers in using learning media at SMKN 4 Payakumbuh that PAI teachers use animated video media (motion graphics) and slides (powerpoint) as learning media. PAI teachers select and design learning media according to the material to be conveyed and the characteristics of students. PAI teachers also receive direction and guidance from schools such as school principals and other teachers in preparing learning media. Second, the supporting and inhibiting factors for using PAI teacher learning media at SMKN 4 Payakumbuh. Supporting factors are the desire of teachers and students to use IT learning media, attract students' attention and interest in learning, students are more active and understand the learning material. While the inhibiting factor is the lack of availability of LCD projectors, teachers need a long time to prepare media and sometimes teachers do not prepare learning media because of other activities that teachers have to do. Keyword: Creativity, Learning Media, PAI Teachers